SAGE: finding IMBH in the black hole desert. (4th September 2019) - Lacour, S; Vincent, F H; Nowak, M; Le Tiec, A; Lapeyrere, V; David, L; Bourget, P; Kellerer, A; Jani, K; Martino, J; Vinet, J-Y; Godet, O; et al.
Abstract: SAGE (SagnAc interferometer for Gravitational wavE) is a project for a space observatory based on multiple 12-U CubeSats in geosynchronous equatorial orbit. The objective is a fast track mission which would fill the observational gap between LISA and ground based observatories. With albeit a lower sensitivity, it would allow early investigation of the nature and event rate of intermediate-mass black hole (IMBH) mergers, constraining our understanding of the universe formation by probing the building up of IMBH up to supermassive black holes (SMBH). Technically, the CubeSats would create a triangular Sagnac interferometer with 140.000 km roundtrip arm length, optimised to be sensitive to gravitational waves at frequencies between 10 mHz and 2 Hz. The nature of the Sagnac measurement makes it almost insensitive to position error, a feature enabling the use of spacecrafts in ballistic trajectories instead of perfect free fall. The light source and recombination units of the interferometer are based on compact fibered technologies without bulk optics. A peak sensitivity of 23 pm ( ) −1 is expected at 1 Hz assuming a 200 mW internal laser source and 10-centimeter diameter apertures. Because of the absence of a test mass, the main limitation would come from the non-gravitational forces applied on the spacecrafts. However, conditionally upon our ability to partially post-process the effect of solar wind and solar pressure, SAGE would allow detection of gravitational waves with strains as low as a few 10 −19 within the 0.1 to 1 Hz range. Averaged over the entire sky, and including the antenna gain of the Sagnac interferometer, the SAGE observatory would sense equal mass black hole mergers in the 10 4 to 10 6 solar masses range up to a luminosity distance of 800 Mpc. Additionally, coalescence of stellar black holes (10 M ) around SMBH (IMBH) forming extreme (intermediate) mass ratio inspirals could be detected within a sphere of radius 200 Mpc.